Application of Bruner's Theory in Cube and Block Mathematics Learning at MTs Ma'arif NU Patikraja, Banyumas Regency - Candra Wahid; Ifada Novikasari (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2022)
This study aims to describe the stages of Bruner's theory in mathematics learning at MTs Maárif NU Patikraja Banyumas in the 2021/2022 academic year. In addition, this study also has the aim of knowing the success and difficulties during learning using Bruner's theory.Because in the application of Bruner's theory, learning will be active, effective, and skilled. Researchers have an interest in researching how to apply Bruner's theory to mathematics learning at MTs Maárif NU Patikraja.This thesis research belongs to the type of descriptive qualitative research, where researchers carry out research directly in the field to conduct research on objects and subjects at MTs Maárif NU Patikraja. In conducting the research, the researcher used data collection techniques by means of observation, interviews, and documentation.With this study, it will be known that mathematics teachers in carrying out mathematics teaching and learning activities, especially building cubes and blocks using Bruner's theory, in Bruner's theory there are three stages including (1) Enactive Phase (2) Iconic Phase (3) Symbolic Phase. The application of the theory has been applied by teachers for 2 years. That way the teacher is able to invite students to be creative and improve understanding or memorizing building spaces.